Peran Penting Undang-Undang Perlindungan Anak dalam Memberikan Perlindungan Hukum pada Kasus Kekerasan Psikis terhadap Anak - Indira Dolita Yulius; Muhammad Farid; Fristia Berdian Tamza (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Law Number 35 of 2014 on Child Protection plays a strategic role in providing legal protection for children who are victims of violence, bpth physical and psychological. The enactment of this regulation represents the state’s response to the increasing number of violence cases againts children, which necessitate a more comprehensive and child-oriented legal protection system. This law strengthens legal instruments through the recognition and protection of children’s rights, the imposition of criminal sanctions againts perpetators of violence, and th provision of recovery mechanisms for child victims. However, in practice, the implementation of the Child Protection Law continues to face various challenges, including weak law enforment, limited protection fasilities and infrastructure, and inadequate coordination among relevant institutions. These obstacles have resulted in the suboptimal realization of legal protection for child victims of violence. Therefore, the effectiveness of Child Protection Law largely depends on the responsiveness and commitment of law enforcement officials, as wekk as the synergy between the government, society, and families. Through such collaboration, optimal and sustainable child protection can be achieved.